(untitled) (Journal of Applied Learning and Teaching, 2021)
The present research evaluates the impact of a blended remote learning intervention on the English as a Foreign Language (EFL) attainment of 8-12-year-old children living in rural parts of Greece who, contrary to their urban counterparts, have no access to English language instruction in their schools. Rooted in a sociocultural understanding of development and the idea that subject matter and academic learning cannot be separated from activities such as social identification, co-construction of understanding and identity development, the present intervention was fundamentally centred around three key concepts: collaborative enquiry, authenticity, and self-paced mastery. Drawing on findings from the quantitative strand of an embedded mixed methods intervention design, the study reveals positive benefits from participation in the blended distance learning intervention with respect to children’s vocabulary and grammar knowledge as well as their aural comprehension skills. Moreover, findings indicate that, in the case of small multigrade schools in Greece, a blended distance learning approach is likely to be effective at raising EFL attainment at a comparable cost level to that of face-to-face programmes. The study thereby contributes to an emerging body of international research on pedagogically and financially viable implementations of blended distance learning involving primary learners in resource-poor settings.